IMPLEMENTATION OF ZAKAT FUNDS TOWARD POVERTY ALLEVIATION THROUGH THE NATIONAL ZAKAT AGENCY OF BATU BARA DISTRICT - Sinaga, Fina Khairani; Abdurrahman, Zulkarnain (Universitas Islam Negeri Mataram, 2024)
Zakat has great potential to become one of the main instruments in poverty alleviation efforts. Zakat is one of the pillars of Islam, so normatively it is an absolute obligation for every Muslim. The purpose of this research is to find out how zakat is distributed by the Batu Bara Regency National Zakat Amil Agency in its efforts to eradicate poverty, as well as identify factors that support and hinder the distribution of zakat. This research uses a qualitative method with a descriptive approach. Data collection methods are observation, interviews, and documentation, using primary and secondary data. There were 5 informants in this study. The data analysis techniques used are data reduction, data presentation, and conclusion verification. Source triangulation ensures the validity of the data used in this research. Based on research results, Baznas, Batu Bara Regency routinely distributes zakat funds every year using two main approaches, namely consumptive zakat and productive zakat, to overcome poverty. Through the Smart, Healthy, Pious and Caring Batu Bara Program, consumptive zakat is distributed to meet the basic needs of mustahik. Meanwhile, the Batu Bara Makmur Program is a productive zakat distribution program that empowers zakat recipients to be economically independent. However, poverty alleviation efforts could be more optimal because a larger proportion of zakat fund distribution occurs through consumptive zakat. Limited human resources cause a lack of supervision of zakat recipients, so the efforts made by productive zakat recipients last only a short time.